How to find the Appropriate Legislative System and Organizational actions for Delhi's Okhla Dump for Municipal Solid Garbage: Towards Sustainable Waste Management in Delhi (Journal of Advances and Scholarly Researches in Allied Education, 2022)
It is estimated that only 78 of the 9,600 tonnes of MSW generated by Delhi is collected, 9 istreated by composting, and the balance gets dumped ipain one of the three open landfill sites locatedoutside of Delhi (Okhla, Ghazipur, Bhalswa). The current research is based on a field study, combiningsurvey analysis and primary data collection and investigation, that evaluated the method of solid wastemanagement employed at the Okhla Landfill site. With the goal of updating and organising the wastedisposal system along scientific lines, this essay investigates the legislative framework and judicialinterventions that are being considered to make this a reality. The results of this study show thatdecentralisation, institutional capacity, and access to sharing waste management knowledge are thecritical driver for sustainable waste management.